Gili Gili Eco Trust’s Social Marketing Strategy in Building Community Awareness in Realizing Gili Trawangan Zero Waste in 2019/2020 - ROSILAWATI, YENI; Najhalidi , Abdul Dirjan (IROCAMM - International Review Of Communication And Marketing Mix, 2021)
Gili Eco Trust is a non-profit foundation with aim to change people behaviour to care more about the environment to realize Gili Trawangan Zero Waste. Garbage is a severe problem in Indonesia, including Gili Trawangan. The increase of tourists has an impact on the amount of waste produced. This study aims to determine the social marketing strategy of Gili Eco Trust in forming public awareness about the environment to realize Gili Trawangan Zero Waste and describe the inhibiting factors. This study utilized a qualitative research method with a case study approach. The findings were obtained from interview, observation, and documentation. This study revealed that Gili Eco Trust has strategic steps to change people’ behavior to realize Gili Trawangan Zero Waste. The reduce, reuse, and recycle movement has become the foundation of Gili Eco Trust to educate people. It was lowered into four social products: 1,500 Trash Cans, Debris Free Friday, Waste Bank, and Gili Tour Recycle. The collaboration between Gili Eco Trust and the Environment-Concerned Community Front has a vital role in changing people’s behavior. Based on Kotler’s social marketing, Gili Eco Trust should improve several social analysis planning and evaluation elements, which should be carried out systematically and structured.